KAJIAN STATUS MUTU AIR SUNGAI MAHAKAM SEGMEN KABUPATEN MAHAKAM ULU BERDASARKAN METODE STORET - Solman, Solman; Bonifasius, Bonifasius; Kartika, Rudi; Gelung, Antonius; Ricard, Romoldus Jonius; Ilang, Yerwanto (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
Mahakam Ulu District is geographically located in the western part of East Kalimantan Province, where the Mahakam River flows. This upstream segment of the Mahakam River is the main river that functions as a transportation route, as raw water processed by Municipal Waterworks, used as a place for bathing, washing as well as serving as a lavatory by the community and a source of water for local community agriculture. Surface water sampling points consist of 14 stations, including ST I: Mahakam River (Long Pahangai Village), ST II: Melaseh River (Long Pahangai Village), ST III: Pahangai River (Long Pahangai Village), ST IV: Mahakam River (Tiong Ohang Village), ST V: Sebunut River (Long Bagun Village), ST VI: Alan River (Long Bagun Village), ST VII: Mahakam River (Ujoh Bilang Village), ST VIII: Melahan River (Long Melahan Village), ST IX: Mahakam River (Laham Village), ST X: Sungai Ratih (Damum Paroy village), ST XI: Mahakam River (Datah Bilang village), ST XII: Pari River (Datah Bilang village), ST XIII: Pataq River (Long Bagun sub-district) and ST XIV: Medang River (Long Bagun sub-district). Determination of water quality status using the STORET Method or Pollution Index Method. The STORET method is one of the commonly used methods for determining water quality status. With this STORET method can be known parameters that have met or exceeded water quality standards. From the results of the study, the water quality parameters that partially did not meet the class I quality standards were 6 parameters, among others: TSS, BOD, COD, DO and Faecal coliform and Total coliform, while for classes II, III and IV all parameters meet the quality standards according to regulations. Keywords: Activities around the river, river quality status, STORET Method